Respon China Terhadap Kebijakan Penempatan Sistem Terminal High Altitude Area Defence Korea Selatan - Muhamad Aryabima; Muhammad Aryabima Pratama; Son Adillah Patra (Frequency of International Relations (FETRIAN), 2023)
South Korea is working with the United States to develop a Terminal High Altitude Area Defense (THAAD) defense system to defend the country from possible attacks by North Korea. However, China objected to this because it was considered a threat to the country's security. Researchers are trying to find out what the response given by China is in accordance with the objections they raised. This study uses a qualitative descriptive method with secondary data sources. The result was that China implemented a boycott policy and various prohibitions on products and tourism which had an impact on the South Korean economy. As a way out, South Korea issued a public statement known as the “three no’s” to normalize relations with China.